Genetic structure in two Phascolosoma species in the Pacific Ocean. Issue 7 (8th August 2016) - Johnson, Nathan D.; Schulze, Anja
ABSTRACT: Phascolosoma agassizii, a commonly reported species of sipunculan worm, occurs at various depths throughout the north Pacific. However, previous studies have shown that this nominal species is actually comprised of two genetically divergent lineages. Phascolosoma agassizii is isolated to the eastern Pacific, whereas a second species, here referred to Phascolosoma sp., is located in the western Pacific and represents a unique, non-sister taxon to P. agassizii . Both species exhibit the same developmental mode with a long-lived, planktotrophic, pelagosphera larval stage, which may facilitate long-distance dispersal, although developmental timing differs. Using an inter-simple sequence repeat polymerase chain reaction (ISSR-PCR) genetic fingerprinting approach, this study examines non-coding polymorphic regions of the nuclear genomes of P. agassizii from four eastern Pacific populations and of Phascolosoma sp. from six western Pacific locations. Small-scale spatial genetic variation was analysed separately for each coastline using an Analysis of Molecular Variance. The data pointed to the potential presence of fine-scale genetic structure within P. agassizii, and recovered significant genetic structure within Phascolosoma sp. from the western Pacific. This study shows that ISSR-PCR is a relatively fast and cost-effective way to study fine-scale genetic diversity in marine invertebrates, although possible analyses and interpretations of the data are subject to the same limitations as other size polymorphism-based approaches.